Enid Sinclair As A Sidekick Character In Wednesday Series - Rahdiyanti, Ni Putu Adina Sri (English Language, Linguistics, Literature, And Education Journal, 2024)
This research purpose to analyze Enid Sinclair's role as a sidekick through selected scenes and dialogues in the Wednesday series. This analysis was conducted using descriptive qualitative method. The Hero's Journey theory by Christopher Vogler (2007) underlies the sidekick analysis in three interrelated supports, namely emotional, moral, and physical support. This research emphasizes the role of sidekicks and their importance in providing complexity to the main character. Enid Sinclair is not only a contrasting character who provides humor, but also plays an important role in not only helping but also being a challenger and mirror in the development of the narrative and the main character. In addition Enid Sinclair assists Wednesday Addams in the internal conflict which gives a new dimension to her character by helping with social perspective, friendship, and sacrifice.